(untitled) (La U Investiga, 2023)
Nutrition is conditioned by sociodemographic factors that can alter nutritional status, especially at an early age. The objective of this research was to identify the sociodemographic conditions and nutritional status of children in the 28 de Septiembre Educational Unit in the city of Ibarra. It is a quantitative, descriptive, correlational, and cross-sectional study. The study population consisted of all children from second to fourth grade of primary school of the 28 de Septiembre Educational Unit, 287 schoolchildren, whose socio-demographic conditions and nutritional status were assessed through anthropometric parameters according to the criteria of the World Health Organization. Among the main results, we found that most of the population was of mixed race, the head of household was self-employed, with a high school level of education. The average age of the schoolchildren was 7.5 years. According to nutritional status, 75.3% had an adequate height for age and 18.8% were at risk of low height; with respect to body mass index for age, 59.6% of the children were found to be normal, 19.9% were at risk of overweight, 18.1% were overweight and obese, 10.8% were at risk of abdominal obesity, and 98.6% were eutrophic according to arm circumference. No relationship was found between nutritional status and sociodemographic conditions of the head of household.